Effect of foliar application of silicon, selenium and zinc on heavy metal accumulation in wheat grains in field studies. Issue 1 (31st December 2022) - Gu, Xuanzhu; Wen, Xin; Yi, Neng; Liu, Yonghua; Wu, Jing; Li, Haidong; Liu, Guoqiang
ABSTRACT: Foliar application technology is commonly used in soil remediation for rice, but few attempts on wheat. The heavy-metal food risk of wheat is a major concern recently. In addition, most prior experiments were conducted in pots and lacked consecutive results of years. Therefore, two consecutive years of field positioning tests were conducted to explore the influence of three kinds of mineral foliar application (Si, Se, and Zn) on the heavy-metal content of wheat grains. The results showed that foliar application with silicon (Si) largely increased wheat yield and plant height, and reduced (Arsenic) As and (Lead) Pb contents. Foliar application with selenium (Se) and zinc (Zn) prominently reduced heavy metals Cd, As and Pb. Se application could not only reduce the heavy-metal content in crops but also improve the Se content in the edible parts of crops, thereby, as suggested, applying it in the low and medium polluted soils.